Sistem Keamanan Jaringan Komputer Berbasis Teknik Intrusion Detection System (IDS) Untuk Mendeteksi Serangan Distrubuted Denial Of Service (DDOS) - Fauzi, Raihan; Muhyidin, Yusuf; Singasatia, Dayan (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Madrasah Aliyah Purwakarta State. is a public high school located in the Purwakarta Regency, Purwakarta District, all activities at this school have used computer networks to support the activities in this school. Madrasah Aliyah Purwakarta State. at this time it has not implemented a computer network security system, because there is no computer network security system implemented at Madrasah Aliyah Negeri Purwakarta, it is still vulnerable to attacks including Ping Attack, Network Scanning and DDOS. Network Development Lyfe Cycle (NDLC) is a method for planning and managing the process of developing a computer network, the NDLC method has 5 stages, namely analysis, design, simulation prototyping, implementation, monitoring, and management. Madrasah Aliyah Purwakarta State. The result of this research is a computer network security system design based on Intrusion Detection System (IDS) using snort and portsentry to detect an attack that enters the computer network of Madrasah Aliyah Negeri Purwakarta such as Ping icmp, nmap (port scan) and DDOS, with get a notification of an attack that enters the computer network, the attack can be prevented by implementing portsentry so that attacks such as Ping icmp, nmap and DDOS will not be able to enter the computer network.